Binding to heparan sulfate or heparin enhances neutrophil responses to interleukin 8. - Webb, L M (1993)
The interaction of interleukin 8 (IL-8) with heparin was studied by using synthetic IL-8 analogs with C- and N-terminal truncations. Elimination of the N-terminal region preceding the first cysteine, which constitutes the IL-8 receptor binding site, did not affect the affinity to heparin-Sepharose. Affinity, however, decreased with progressive truncation at the C terminus, and no binding was observed when the C-terminal alpha-helix was eliminated. The effect of heparin and other glycosaminoglycans on IL-8 activity was also tested. When IL-8 was applied together with heparan sulfate, neutrophil chemotaxis in vitro was enhanced up to 4-fold, and the stimulus-dependent increase in cytosolic free Ca2+ increased markedly in both rate and peak value. Heparin had a similar effect on the Ca2+ response but did not enhance chemotaxis. The glycosaminoglycans by themselves did not elicit neutrophil responses. Their enhancing effect was restricted to stimulation with IL-8 and was not observed when the unrelated chemoattractant fMet-Ile-Phe-Leu was used as the stimulus. Elastase released from stimulated neutrophils was inhibited by heparin, heparan sulfate, and, to a lesser extent, chondroitin sulfate B, confirming previous observations. Taken together, these results suggest that heparan sulfate, which is present on the endothelial cell surface and in the basement membrane, may have a dual function in diapedesis, promotion of IL-8-dependent transmigration of neutrophils, and protection of the tissue microenvironment from damage by lytic enzymes released from the migrating cells.